Examination of Critical Thinking Skills of Prospective Classroom Teachers - Hamdi Karakaş (Üniversite Araştırmaları Dergisi)
In this study, it is aimed to determine the critical thinking skills of prospective classroom teachers. Average scores of prospective classroom teachers' critical thinking skills and sub-dimensions are compared according to gender and grade variables. In the study, the scanning model, which is one of the quantitative research approaches, is grounded on and the Critical Thinking Appraisal Test is used as a data collection tool. The study was carried out in the fall semester of the 2019-2020 academic year and 671 prospective classroom teachers participated in the study. Average scores of prospective classroom teachers' critical thinking skills are calculated as 0.63 in the study, and this value shows that the prospective classroom teachers have an intermediate level of critical thinking skill. Additionally, the average sub-dimension scores of critical thinking skills are also calculated, and it is concluded that while the prospective classroom teachers are at a high level with a large effect in interpreting and performing deductions, they are at low-end level with a large effect in inference. It is determined that the critical thinking skill average scores of female prospective classroom teachers are higher than those of male teacher candidates with a small effect, and the rank average scores of sub-dimensions of Awareness of Assumptions and Interpretation of female candidates are higher than those of male teacher candidates with a small effect. It is observed that the rank average scores of critical thinking skills of the prospective classroom teachers who are in second grade are the highest, while the rank average scores of critical thinking skills of the prospective classroom teachers who are in fourth grade are the lowest. It is found that critical thinking skill levels decrease with a large effect for prospective classroom teachers in third and fourth grades. If undergraduate education of prospective classroom teachers is far from memorization, experiencing different activities that can be used in their prospective professional lives, either will provide development as a profession and will increase their critical thinking tendencies by enhancing critical thinking skills.